Testosterone abolishes implicit subordination in social anxiety. (October 2016) - Terburg, David; Syal, Supriya; Rosenberger, Lisa A.; Heany, Sarah J.; Stein, Dan J.; Honk, Jack van
Highlights: Submission to the dominance of others is an implicit mechanism in social anxiety. A single dose of testosterone can temporarily abolish this implicit subordination. Treatment strategies can benefit from targeting hormonal mechanisms of dominance. Abstract: Neuro-evolutionary theories describe social anxiety as habitual subordinate tendencies acquired through a recursive cycle of social defeat and submissive reactions. If so, the steroid hormone testosterone might be of therapeutic value, as testosterone is a main force behind implicit dominance drive in many species including humans. We combined these two theories to investigate whether the tendency to submit to the dominance of others is an implicit mechanism in social anxiety ( Study-1 ), and whether this can be relieved through testosterone administration ( Study-2 ). Using interactive eye-tracking we demonstrate that socially anxious humans more rapidly avert gaze from subliminal angry eye contact ( Study-1 ). We replicate this effect of implicit subordination in social anxiety in an independent sample, which is subsequently completely abolished after a single placebo-controlled sublingual testosterone administration ( Study-2 ). These findings provide crucial evidence for hormonal and behavioral treatment strategies that specifically target mechanisms of dominance and subordination in social anxiety.